Efficient elimination of zearalenone at high processing temperatures by a robust mutant of Gliocladium roseum zearalenone lactonase. (December 2022) - Fang, Yuanyuan; Huang, Zhaolin; Xu, Wei; Wang, Chengfei; Sun, Yurong; Zhang, Wenli; Guang, Cuie; Mu, Wanmeng
Abstract: The zearalenone (ZEN) lactonase from Gliocladium roseum (ZENG), possessing high activity but poor thermostability, is insufficient to meet the requirements of the feed industry. In this study, two potential hotspots, S162 and S220 in ZENG, were obtained through molecular dynamic (MD) simulations. In the first round, two mutants including S162P and S220R with increased thermostability were screened. Furthermore, the half-life ( t 1/2 ) of S162P/S220R mutant at 55 °C was increased by 36.8-fold compared to the wild-type enzyme, and the melting temperature ( T m ) was significantly increased by 8.2 °C. MD and structure analysis showed that the improvement in the thermostability of S162P/S220R was possibly in relation to the decreased root mean square fluctuations (RMSF) value, enhanced structural stability, and increased hydrogen bonds. To the best of our knowledge, the thermostability of the mutant S162P/S220R ranked the first of all reported ZEN lactonases, indicating a good candidate for efficient elimination of ZEN, especially at high processing temperatures. Highlights: The potential "hotspots" of ZEN lactonases were obtain using molecular dynamic simulations. Two single-site mutants with excellent thermostability were identified. The combinational effect of the double-site mutant on thermostability was examined.